(untitled) - Dore, Ronald (London, 1989)
This book introduce the general system. Who goes where? Vocational streams in the mainline formal education system. Post-secondary, non-university VET. Private sector, non-univesity training schools...
Keywords: Đào tạo nghề,Occupational training; Nhật Bản,Japan